Electrochemical Growth and Structural Study of the AlxGa1−xAs Nanowhisker Layer on the GaAs Surface - Suchikova, Yana; Kovachov, Sergii; Bohdanov, Ihor; Abdikadirova, Anar A.; Kenzhina, Inesh; Popov, Anatoli I. (MDPI, 2023)
This work presents a novel, cost-effective method for synthesizing AlxGa1−xAs nanowhiskers on a GaAs surface by electrochemical deposition. The process begins with structuring the GaAs surface by electrochemical etching, forming a branched nanowhisker system. Despite the close resemblance of the crystal lattices of AlAs, GaAs, and AlxGa1−xAs, our study highlights the formation of nanowhiskers instead of layer-by-layer film growth. X-ray diffraction analysis and photoluminescence spectrum evaluations confirm the synthesized structure’s crystallinity, uniformity, and bandgap characteristics. The unique morphology of the nanowhiskers offers promising implications for solar cell applications because of the increased light absorption potential and reduced surface recombination energy losses. We conclude by emphasizing the need for further studies on the growth mechanisms of AlxGa1−xAs nanowhiskers, adjustments of the “x” parameter during electrochemical deposition, and detailed light absorption properties of the formed compounds. This research contributes to the field of wideband materials, particularly for solar energy applications, highlighting the potential of electrochemical deposition as a flexible and economical fabrication method. --//-- This is an open access article: Suchikova, Y.; Kovachov, S.; Bohdanov, I.; Abdikadirova, A.A.; Kenzhina, I.; Popov, A.I. Electrochemical Growth and Structural Study of the AlxGa1−xAs Nanowhisker Layer on the GaAs Surface. J. Manuf. Mater. Process. 2023, 7, 153. https://doi.org/10.3390/jmmp7050153 published under the CC BY 4.0 licence.
The study was supported by the Ministry of Education and Science of Ukraine via Project No. 0122U000129 “The search for optimal conditions for nanostructure synthesis on the surface of A3B5, A2B6 semiconductors and silicon for photonics and solar energy”, Project No. 0121U10942 “Theoretical and methodological bases of system fundamentalization of the future nanomaterials experts training for productive professional activity”, and Project No. 0123U100110 “System of remote and mixed specialized training of future nanoengineers for the development of new dual-purpose nanomaterials”. In addition, the research of A.I.P. and Y.S. was partly supported by COST Action CA20129 “Multiscale irradiation and chemistry driven processes and related technologies” (MultiChem). Y.S. was partly supported by COST Action CA20126—Network for research, innovation, and product development on porous semiconductors and oxides (NETPORE). A.I.P., thanks to the Institute of Solid State Physics, University of Latvia, ISSP UL as the Center of Excellence, is supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; nanowhiskers; electrochemical deposition; electrochemical etching; crystal lattice; layer-by-layer growth; X-ray diffraction analysis; photoluminescence spectrum; crystallinity